MS Polstjerna Exhibit ... - Campbell, Sandy (University of Alberta Library, 2024)
From the descriptive panel outside the exhibit: "The sealing vessel MS Polstjerna was built in 1949 and was designed to withstand the conditions of the Arctic Ocean. The vessel sailed for 33 hunting seasons and brought home more than 97,000 seals." The vessel sits in a dry-dock, with a glass roof, flat on one side and arced on the other, forming the shape of a sail. The mast of the vessel protrudes through the roof. The exhibit is located near the harbour, next to Polaria, the Tromsø aquarium, which features seals. ...